Peningkatan Kesehatan Fisik dan Pemeriksaan Kesehatan Peserta Gowes 1912 pada Pra Muktamar Muhammadiyah di Masjid An Nur Sidoarjo - Widi Arti; Andi Fadhila Tendriwulan; Bagus Anjasmara; Khumairo Hardiyanti Rukmana (Jurnal Abdimas Kesehatan (JAK), 2023)
This community service program is one of the preventive, curative and rehabilitative programs for the 1912 bike ride participants at the 48th Muhammadiyah Aisyiyah Pre-Congress. This program is expected to improve physical fitness after participating in a series of pre-conference events which were attended by 1912 people. This community service works in collaboration with cross-professions such as physiotherapy, pharmacists and acupuncture for services. The purpose of this activity is to help the 1912 gowes participants maintain their body fitness performance after physical activity. The method used in community service is health consultation, education, physical examination, assessment and treatment using electrophysical modalities and manual therapy. This activity was held at the An Nur Muhammadiyah mosque in Sidoarjo.The output of the community service program that has been carried out can be obtained that participants over the age of 30 are prone to having musculoskeletal disorders such as lower back pain, knee calcification, neck pain and shoulder pain.